A three arm cluster randomised controlled trial to test the effectiveness and cost-effectiveness of the SMART Work & Life intervention for reducing daily sitting time in office workers: Study protocol 11 Medical and Health Sciences 1117 Public Health and Health Services - Edwardson, C.; Biddle, S.; Clarke-Cornwell, A.; Clemes, S.; Davies, M.; Dunstan, D.; Eborall, H.; Granat, M.; Gray, L.; Healy, Genevieve; Richardson, G.; Yates, T.; et al. (BioMed Central Ltd, 2018)
© 2018 The Author(s). Background: Office-based workers typically spend 70-85% of working hours, and a large proportion of leisure time, sitting. High levels of sitting have been linked to poor health. There is a need for fully powered randomised controlled trials (RCTs) with long-term follow-up to test the effectiveness of interventions to reduce sitting. This paper describes the methodology of a three-arm cluster RCT designed to determine the effectiveness and cost-effectiveness of the SMART Work & Life intervention, delivered with and without a height-adjustable desk, for reducing daily sitting. Methods/design: A three-arm cluster RCT of 33 clusters (660 council workers) will be conducted in three areas in England (Leicester; Manchester; Liverpool). Office groups (clusters) will be randomised to the SMART Work & Life intervention delivered with (group 1) or without (group 2) a height-adjustable desk or a control group (group 3). SMART Work & Life includes organisational (e.g., management buy-in, provision/support for standing meetings), environmental (e.g., relocating waste bins, printers), and group/individual (education, action planning, goal setting, addressing barriers, coaching, self-monitoring, social support) level behaviour change strategies, with strategies driven by workplace champions. Baseline, 3, 12 and 24 month measures will be taken. Primary outcome: Objectively measured daily sitting time (activPAL3). Secondary outcomes: objectively measured sitting, standing, stepping, prolonged sitting and moderate-to-vigorous physical activity time and number of steps at work and daily; objectively measured sleep (wrist accelerometry). Adiposity, blood pressure, fasting glucose, glycated haemoglobin, cholesterol (total, HDL, LDL) and triglycerides will be assessed from capillary blood samples. Questionnaires will examine dietary intake, fatigue, musculoskeletal issues, job performance and satisfaction, work engagement, occupational and general fatigue, stress, presenteeism, anxiety and depression and sickness absence (organisational records). Quality of life and resources used (e.g. GP visits, outpatient attendances) will also be assessed. We will conduct a full process evaluation and cost-effectiveness analysis. Discussion: The results of this RCT will 1) help to understand how effective an important simple, yet relatively expensive environmental change is for reducing sitting, 2) provide evidence on changing behaviour across all waking hours, and 3) provide evidence for policy guidelines around population and workplace health and well-being. Trial registration: ISRCTN11618007. Registered on 21 January 2018.